2000
DOI: 10.1016/s0022-5347(05)67701-4
|View full text |Cite
|
Sign up to set email alerts
|

Laparoscopic Nephroureterectomy for Upper Tract Transitional Cell Cancer: The Washington University Experience

Abstract: Although laparoscopic nephroureterectomy is a longer operation, it has the same efficacy and is better tolerated by patients than open nephroureterectomy for upper tract transitional cell carcinoma. As operating time decreases due to surgeon experience and the recent development of hand assisted laparoscopy, laparoscopic nephroureterectomy may soon become the procedure of choice for the ablative management of upper tract transitional cell carcinoma.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
127
0
7

Year Published

2001
2001
2013
2013

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 257 publications
(137 citation statements)
references
References 16 publications
3
127
0
7
Order By: Relevance
“…Stones have been reported to form on almost 50% of titanium staple lines during laparoscopic assisted continent urinary diversion in animal models. 18 However, the stapled bladder cuff showed no evidence of staple erosion or encrustation on any exposed staple despite follow up as long as 8 years in a recent report on laparoscopic nephroureterectomy in over 20 patients, 19 and Grubb et al . have studied the safety of titanium staples in laparoscopic pyeloplasty with no stone formation on follow up, although stone formation is an ongoing concern.…”
Section: Discussionmentioning
confidence: 93%
“…Stones have been reported to form on almost 50% of titanium staple lines during laparoscopic assisted continent urinary diversion in animal models. 18 However, the stapled bladder cuff showed no evidence of staple erosion or encrustation on any exposed staple despite follow up as long as 8 years in a recent report on laparoscopic nephroureterectomy in over 20 patients, 19 and Grubb et al . have studied the safety of titanium staples in laparoscopic pyeloplasty with no stone formation on follow up, although stone formation is an ongoing concern.…”
Section: Discussionmentioning
confidence: 93%
“…This 75% rate of bladder cancer is substantially higher than the reported literature for patients undergoing treatment for utUC (1,11,15). Other factors including longer operative time (16) and longer length of follow-up (7,17) are associated with higher rates of bladder cancer. We postulate that seeding from the upper tract may increase the rate of bladder cancer above the already significant baseline rate in these patients.…”
mentioning
confidence: 74%
“…Of the seven patients who had grade 4, stage T2±4 disease in the laparoscopic group, three had local retroperitoneal tumour metastases. None of the four patients with a similar grade of disease who underwent the open procedure had evidence of retroperitoneal recurrence [48]. Although these are small series, they raise doubts about whether laparoscopic surgery is necessarily advantageous for higher stage diseases.…”
Section: Laparoscopic Nephroureterectomymentioning
confidence: 85%
“…Shalhav et al [48] reported a series of 25 patients who underwent laparoscopic nephroureterectomy and who were compared with 17 undergoing open nephroureterectomy. The results indicated that laparoscopic surgery required twice the operating time of open surgery (7.7 vs 3.9 h), although the patients from the laparoscopic group had a 74% decrease in analgesia requirement (37 vs 144 mg morphine sulphate) and a 63% shorter hospital stay (3.6 vs 9.6 days).…”
Section: Laparoscopic Nephroureterectomymentioning
confidence: 99%